The sustainability of urban green space during pandemic crises - Nor Azhar, Ali Saifuddin; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Mohamad Nadzri, Amira Arisya (IOP Publishing Ltd, 2023)
The pandemic issue is frequently discussed in the news or mass media. In 2002, Ebola,SARS, and SARS-CoV-2 were highly infective viruses that caused a global pandemic, according to the pandemic chronology. Animals in the forest spread each of these viruses to people. Since the 1918 influenza pandemic, the unique human coronavirus COVID-19 has caused the fifth documented pandemic. In this era, there has been an increase in public awareness about urban green spaces. Many studies suggest that proper landscape planning and design with a sustainable mindset may provide a helpful and responsive environment for healthy urban improvement during pandemic crises. Thus, this study aims to look into the functions of urban green spaces for long-term environmental health, especially during pandemic crises. The research revealed that urban green spaces improve immune system performance, promote social capital and cohesiveness, reduce mortality, lengthen life expectancy, and potential adverse health impacts. The findings also emphasised various advantages of urban green spaces during pandemics, such as enhanced mental and physical well-being, less risk of disease transmission, and enhanced social cohesion. In summary, urban green space sustainability may support a healthy environment and lifestyle in metropolitan areas amid pandemic crises.